2021
DOI: 10.1002/rrq.451
|View full text |Cite
|
Sign up to set email alerts
|

Improving Questioning–Answering Strategies in Learning from Multiple Complementary Texts: An Intervention Study

Abstract: Studies have shown that inferential questions encourage a more in‐depth understanding of texts and that students need to learn appropriate strategies for answering them, particularly when they deal with multiple texts. In this experimental study, the authors aimed to improve eighth‐grade students’ (13‐ to 14‐years old) ability to answer intra‐ and intertextual inferential questions when they read one or multiple complementary texts. The intervention was implemented by a group of middle‐school history teachers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 81 publications
0
7
0
1
Order By: Relevance
“…Many previous studies confirm that RTS is an effective reading strategy that significantly supports reading comprehension (Ahmadi, 2016;Cockerill et al, 2022;Dew et al, 2021;Hamdani, 2020;O'Hare et al, 2019;Pilten, 2016;Rojabi, 2021;Thurston et al, 2020). In addition, as in RTS, students read better in learning processes used by inquiry strategies (Ahmadi et al, 2021;Ariawan, & Winoto, 2021;Brown, & Pyle, 2021;Bui et al, 2021;Castells et al, 2021;Liu, 2021;Parjan, & Mohamad, 2021;Stuckelman et al, 2022).…”
Section: Innoeduca International Journal Of Technology and Educationa...mentioning
confidence: 83%
See 1 more Smart Citation
“…Many previous studies confirm that RTS is an effective reading strategy that significantly supports reading comprehension (Ahmadi, 2016;Cockerill et al, 2022;Dew et al, 2021;Hamdani, 2020;O'Hare et al, 2019;Pilten, 2016;Rojabi, 2021;Thurston et al, 2020). In addition, as in RTS, students read better in learning processes used by inquiry strategies (Ahmadi et al, 2021;Ariawan, & Winoto, 2021;Brown, & Pyle, 2021;Bui et al, 2021;Castells et al, 2021;Liu, 2021;Parjan, & Mohamad, 2021;Stuckelman et al, 2022).…”
Section: Innoeduca International Journal Of Technology and Educationa...mentioning
confidence: 83%
“…They even gave feedback to their peers. It was observed that the reading processes in which questioning strategies were used were more effective, and the readers achieved better reading scores (Ahmadi et al, 2021;Ariawan, & Winoto, 2021;Brown, & Pyle, 2021;Bui et al, 2021;Castells et al, 2021;Liu, 2021;Parjan, & Mohamad, 2021;Stuckelman et al, 2022). The explanation phase included teacher support.…”
Section: Innoeduca International Journal Of Technology and Educationa...mentioning
confidence: 99%
“…Kemampuan peserta didik dalam memilih informasi untuk menjawab pertanyaan berpengaruh besar dalam soal literasi membaca. Peserta didik yang memiliki kemampuan literasi membaca lebih baik akan menggunakan strategi pemilihan informasi berbasis ide, sedangkan peserta didik dengan kemampuan rendah akan terdorong menggunakan strategi memilih informasi yang tidak sesuai dengan mencocokan kata (Castells et al, 2022). Kemampuan memilih dan memahami informasi berpengaruh terhadap strategi menjawab pertanyaan dan mengaitkannya dengan konsep yang telah dimiliki (Cerdán et al, 2011).…”
Section: Siswa B: Soal Tipe Ini Hampir Sama Harus Memahami Maksud Inf...unclassified
“…In most circumstances, human intelligence progression is only possible with the assistance of other individuals. One indication of the success of a teacher's instruction is if their students' written work improves while taking English as a Foreign Language classes (Castells et al, 2022& Guo et al, 2021. Due to the limited amount of time allotted for schooling, teachers cannot provide students with support at any stage of their academic careers.…”
Section: Preparing Students For Any Situationmentioning
confidence: 99%